2020
DOI: 10.1186/s12891-020-03450-8
|View full text |Cite
|
Sign up to set email alerts
|

Do we need to suture the pronator quadratus muscle when we do open reduction and internal fixation for fracture of the distal radius

Abstract: Background: Open reduction and internal fixation is often used for the treatment of distal radius fracture. Opening the pronator quadratus muscle during the process of open reduction and internal fixation is necessary to achieve sufficient exposure. Therefore, knowledge on how to suture the pronator quadratus muscle will be of essence. Aim: The aim of the present study was to determine if suturing the pronator quadratus during the treatment of the distal radius fracture can enhance limb function. Methods: A to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…The typical anatomical structure of the PQ muscle is the basis of its function [ 40 ]. It was found that the PQ muscles were heavily scarred, significantly atrophied, and adhered to the surrounding tissue after suturing.…”
Section: Discussionmentioning
confidence: 99%
“…The typical anatomical structure of the PQ muscle is the basis of its function [ 40 ]. It was found that the PQ muscles were heavily scarred, significantly atrophied, and adhered to the surrounding tissue after suturing.…”
Section: Discussionmentioning
confidence: 99%
“…Fang et al found that the patients removed the plate after fracture healing, 23 patients had apparent atrophy of the PQ after repair, and prominent muscle scar and fibrosis. There was no difference in hand function between these 23 patients and other patients (29). Spies et al (30) have shown that patients with late tendon irritation after PQ repair persist, mainly where flexor pollicis longus rupture was caused by the plate being positioned too far, which may increase the risk of tendon injury.…”
Section: Discussionmentioning
confidence: 74%
“…They reported only 23 healed PQ with concomitant muscle atrophy in 126 patients after suturing, with the remaining patients showing scarring intraoperatively. Healing was assessed at implant removal by experienced surgeons [26]. The research group of Mulders et al investigated the question of functional differences between sutured and non-sutured PQ in a systematic review.…”
Section: Discussionmentioning
confidence: 99%